2012
DOI: 10.2527/jas.2011-4222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-mannanase on the digestibility of diets with different protein sources in dogs determined by different methodologies1

Abstract: This experiment aimed at evaluating the effects of including the enzyme, β-mannanase, in dog (Canis lupus familiaris) diets based on either poultry (Gallus gallus domesticus) by-product meal (PBM) or soybean [Glycine max (L.) Merr.] Meal (SBM). The second objective was to evaluate 3 methods for determining energy and nutrient digestibility values in diets fed to dogs: total fecal collection (TFC) and use of aia or crude fiber (CF) as a marker. Eight dogs were allotted to a replicated latin square (4 by 4) desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…soyabean meal ( 16 ) ; however, Félix et al . ( 17 ) , comparing diets also based on poultry and soyabean meals, found that the inclusion of mannanase at 0·01 % resulted in improved macronutrient digestibility. Overall, digestive enzyme supplementation (mainly carbohydrases) in feed does not seem to have a marked effect on canine nutrient and energy digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…soyabean meal ( 16 ) ; however, Félix et al . ( 17 ) , comparing diets also based on poultry and soyabean meals, found that the inclusion of mannanase at 0·01 % resulted in improved macronutrient digestibility. Overall, digestive enzyme supplementation (mainly carbohydrases) in feed does not seem to have a marked effect on canine nutrient and energy digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, no difference in CP digestibility was noted between 2- and 17-year-old beagles [ 41 ]. Dietary supplementation with β-mannanase (the enzyme hydrolyzing polysaccharides made from D -mannose) enhanced the apparent digestibilities of CP in dogs fed a diet containing a large amount of plant-sourced protein ingredients, but had no effect in dogs fed a diet containing a large amount of animal-sourced protein ingredients [ 42 ]. Compared with the extruded diet, slight cooking enhanced CP digestibility in dogs [ 30 ].…”
Section: Digestibilities Of Amino Acids In the Diets Of Cats And Dogsmentioning
confidence: 99%
“…In this scenario, pet food supplemented with enzymes can enhance its digestibility and nutrient availability. A multitude of enzymes (β-mannanase, phytase, protease, xylanase, β-glucanase, cellulase, amylase, pectinase, lipase, and glucoamylase) have been studied to evaluate their effect on the digestibility of canine food (11)(12)(13)(14)(15)(16)(17)(18). The inclusion of mannanase in the soybean meal increased protein and energy digestibility in dogs (11).…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of enzymes (β-mannanase, phytase, protease, xylanase, β-glucanase, cellulase, amylase, pectinase, lipase, and glucoamylase) have been studied to evaluate their effect on the digestibility of canine food (11)(12)(13)(14)(15)(16)(17)(18). The inclusion of mannanase in the soybean meal increased protein and energy digestibility in dogs (11). The addition of proteases and lipases in feather meal showed enhanced digestible energy in dog trials (15).…”
Section: Introductionmentioning
confidence: 99%